2021
DOI: 10.1186/s12876-021-01871-w
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in patients with decompensated liver cirrhosis and bacterial infections in a tertiary center in Northern Germany

Abstract: Background and aims Bacterial infections are common in patients with decompensated liver cirrhosis and a leading cause of death. Reliable data on antibiotic resistance are required to initiate effective empiric therapy. We here aim to assess the antimicrobial resistance profile of bacteria among patients with liver cirrhosis and infection. Methods Overall, 666 cirrhotic patients admitted to Hannover Medical School between January 2012 and April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Our data showed an empirically more frequent antibiotic coverage in the gram-positive spectrum with, however, more frequent detection of a gram-negative infection. Hillert et al [ 16 ] found, that a gram-positive pathogen was detected in 54% of cases, with the most common single pathogen detection being E. coli . Hillert et al [ 16 ] inclusion criterion was the presence of ascites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data showed an empirically more frequent antibiotic coverage in the gram-positive spectrum with, however, more frequent detection of a gram-negative infection. Hillert et al [ 16 ] found, that a gram-positive pathogen was detected in 54% of cases, with the most common single pathogen detection being E. coli . Hillert et al [ 16 ] inclusion criterion was the presence of ascites.…”
Section: Discussionmentioning
confidence: 99%
“…Hillert et al [ 16 ] found, that a gram-positive pathogen was detected in 54% of cases, with the most common single pathogen detection being E. coli . Hillert et al [ 16 ] inclusion criterion was the presence of ascites.…”
Section: Discussionmentioning
confidence: 99%
“…ESBL Enterobacteriaceae, mainly E. coli and K. pneumonia , were predominant in almost all previous studies [ 7 , 11 , 23 , 24 ]. However, the share of gram-positive cocci represented by MSRA and VSE or VRE has increased significantly in recent years worldwide [ 24 ], particularly in European and American centers [ 11 , 25 , 26 ]. This trend can be explained by the increased use of invasive maneuvers in these centers [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, drug should be selected considering patients characteristics, such as comorbidities and previous exposure to antibiotics, as people above the age of 65 years may have hepatic or renal impairments, which may affect drug metabolism and elimination; for instance, a pharmacokinetic study on older patients with moderate-to-severe impairment in renal function has highlighted a greater ceftriaxone exposure with a 48 h dosing schedule (50). Similarly, bacterial characteristics should be considered as well, as a local pattern of ceftriaxone and quinolone resistance in cirrhotic patients have been reported (51,52).…”
Section: Antibacterial Treatment During Gi Bleedingmentioning
confidence: 99%